Potential utilization of recycled PET in comparison with liquid crystalline polymer as an additive for HDPE based composite fibers: Comparative investigation on mechanical performance of cross-ply laminates - Supattra Kayaisang (2018)
Recycled polyethylene terephthalate (rPET) was used as an alternative reinforcing material for in situ microfibrillar-reinforced polyethylene (PE) based composite fibers and compared with liquid crystalline polymer (LCP). The neat PE and its composites reinforced with LCP and rPET microfibrils under the compatibilizing promotion of 5 wt% styrene-(ethylene butylene)-styrene-grafted maleic anhydride (SEBS-g-MA) compatibilizer, were prepared as fibers using a hot drawing process. Cross-ply laminates of the neat PE and the compatibilized composite fibers were then prepared using a film stacking method. The tensile, flexural and impact performances of each laminate system were examined and compared. Under tensile loading, no significant differences in the initial part of the stress-strain curves, and hence comparable tensile modulus (≈4 GPa) among all laminates, were observed. A difference was only seen in the final part of the curves. For flexural properties, the flexural moduli of the compatibilized LCP- and rPET-composite laminates were nearly the same (≈3 GPa). At high flexural strains (>1%), the different stress-strain behaviors of the laminates were clearly observed. Interestingly, the compatibilized rPET-composite laminate showed much better impact-resistance compared with PE- and compatibilized LCP-laminates. The results demonstrated a high potential for use of the rPET-composite fiber laminate in impact-resistant applications. © 2013 by Walter de Gruyter Berlin Boston 2013.